Informing vs. promoting. The use of TikTok on France TV, BBC, and SVT - Maroto-González, Isaac; Fieiras-Ceide, César; Vaz-Álvarez, Martín (Frontiers in Communication, 2024)
This study explores the use of TikTok by public broadcasters France TV, BBC and SVT in order to measure its informational and promotional relevance on the platform, and to identify the types of videos that generate the highest levels of engagement among users. By examining the news profile associated with the information and the corporate profile of each of the selected broadcasters, 120 publications were analysed, counting the number of users and interactions, including likes and levels of engagement of the content. In addition, a content analysis was carried out focusing on the formal, promotional and informative characteristics of the posts. The findings revealed an interest in both promotional and informational content shared by the platforms on TikTok. In the case of SVT, higher levels of engagement are observed in comparison to the BBC and France TV profiles. Among the contents with the highest engagement, those of an informative kind with a focus on social issues stand out, highlighting proximity and immediacy. In the promotional domain, videos about events and cultural content stand out. From a structural point of view, content designed specifically for the platform predominates, as opposed to adaptations and with a duration of less than one minute.